The Birth Registration Rate in Bangladesh Observed in Rural and Urban Region - Karim, Mehnaz (Advances in Social Sciences Research Journal, 2017)
The aim of this study is to analyze the birth registration rate of Bangladesh where the data has been observed during the period of 2009. The intact geographical area of Bangladesh has been covered in this survey. The number of birth registration in the categories of gender, the areas where these children belong to, their mother’s education have been focused in this write up based on the survey collected from Multiple Indicator Cluster Survey 2009 by Bangladesh Bureau of Statistics. Later on some graphs and analysis of those graphs to evaluate the comparison of the socio economic life of the nation and how that effects the affordability of many necessary things in life and few essential matters that fails to create impact in our rural society. One of such issue is the child birth registration. The data provides the snapshot of the nation and key information that benefits to perform any survey based research. The bar graphs have been used to analyze the classification of the population in statistical perception.